POPULARITAS K-POP DI KALANGAN MAHASISWA DAN IMPLIKASINYA TERHADAP SIKAP NASIONALISME: STUDI KASUS ANGGOTA UNIT KEGIATAN MAHASISWA HALLYU EDUTAINMENT UPI - Zulfa Nabilah, Nazhifatun; Abdulkarim, Aim; Mulyadi Nugraha, Dadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the increasing popularity of Korean Pop (K-Pop) culture among university students as a result of globalization and the development of digital technology. This phenomenon raises concerns about the influence of foreign culture on the nationalist attitudes of the younger generation. This study aims to analyze the entry, spread, and development of K-Pop culture until it became popular among student members of the Hallyu Edutainment Student Activity Unit (UKM) UPI, as well as to understand how students interpret national identity and nationalism amidst their interest in Korean culture. The research used a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observations, and documentation studies of members of the UKM Hallyu Edutainment UPI. The results show that K-Pop's popularity is influenced by the development of digital and social media, which facilitate students' quick and real-time access to Korean cultural information. Students' interest in K-Pop is influenced not only by the music and visuals of idols, but also by the values ​​of discipline, hard work, and professionalism displayed by Korean idols. Furthermore, the formation of K-Pop fan communities creates solidarity and unique communication patterns among students. Despite exposure to foreign cultures, students still demonstrate nationalism through their concern for national issues, participation in social activities, and the ability to filter foreign cultures according to Indonesian values ​​and norms. Thus, K-Pop culture does not diminish students' nationalism but rather encourages a selective cultural adaptation process.